Multiparameter Schur Q-Functions Are Solutions of the BKP Hierarchy - Rozhkovskaya, N. (Symmetry, Integrability and Geometry: Methods and Applications, 2019)
We prove that multiparameter Schur Q-functions, which include as specializations factorial Schur Q-functions and classical Schur Q-functions, provide solutions of the BKP hierarchy.